Big Data dan Penguasaan Pasar dalam Pengambilalihan Usaha Digital: Komparasi Rezim Hukum Persaingan Indonesia dan Jerman - Samariadi, Samariadi; Firmanda, Hengki; Ervansyah, Fauzan; GM. Manik, Rahmat (Universitas Jambi, Fakultas Hukum, 2026)
The digital economy has positioned Big Data as a primary strategic asset that creates new market entry barriers in the form of